Ket Programming Guide - Rosa, Evandro C. R. da; Marchi, Jerusa; Santiago, Rafael de (Anais do Simpósio Brasileiro de Computação e Comunicação Quânticas (SBCCQ), 2026)
The development of quantum computing necessitates specialized software tools. Ket is an open-source quantum programming platform that enables gate-based quantum development in Python, supported by a Rust-based runtime library and simulator. This paper presents a programming guide for the Ket platform. It covers the core concepts required to develop quantum applications, including quantum process management, gate operations, measurement strategies, and Hamiltonian construction. Designed for readers with prior knowledge of quantum computing and Python, this guide bridges the gap between theoretical algorithms and practical software implementation. To consolidate these concepts, the paper concludes with a practical tutorial applying QAOA, VQE, and FALQON to the Max-Cut problem, ultimately equipping researchers and developers to fully utilize the Ket platform.